An SNP Mutation of Gene RsPP Converts Petal Color From Purple to White in Radish (Raphanus sativus L.) - Liu, Dongming; Wei, Xiaochun; Sun, Dongling; Yang, Shuangjuan; Su, Henan; Wang, Zhiyong; Zhao, Yanyan; Li, Lin; Liang, Jinfang; Yang, Luming; Zhang, Xiaowei; Yuan, Yuxiang (Frontiers in Plant Science, 2021)
Along with being important pigments that determining the flower color in many plants, anthocyanins also perform crucial functions that attract pollinators and reduce abiotic stresses. Purple and white are two different colors of radish petals. In this study, two cDNA libraries constructed with purple and white petal plants were sequenced for transcriptome profiling. Transcriptome results implied that the expression level of the genes participating in the anthocyanin biosynthetic pathway was commonly higher in the purple petals than that in the white petals. In particular, two genes, F3′H and DFR, had a significantly higher expression pattern in the purple petals, suggesting the important roles these genes playing in radish petal coloration. BSA-seq aided-Next Generation Sequencing of two DNA pools revealed that the radish purple petal gene (RsPP) was located on chromosome 7. With additional genotyping of 617 F2 population plants, the RsPP was further confined within a region of 93.23 kb. Transcriptome and Sanger sequencing analysis further helped identify the target gene, Rs392880. Rs392880 is a homologous gene to F3′H, a key gene in the anthocyanin biosynthetic pathway. These results will aid in elucidating the molecular mechanism of plant petal coloration and developing strategies to modify flower color through genetic transformation.